2015
DOI: 10.1007/s40620-015-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-transplant antiaggregant and anticoagulant therapies on early hemorrhagic and cardiovascular events after kidney transplantation

Abstract: In conclusion, HE and CVE are relatively rare but can be severe, but there are no pre-KTx modifiable risk factors. If an anticoagulant therapy with low molecular weight heparins has to be started soon after surgery, monitoring of anti-Xa activity is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
3
6
0
1
Order By: Relevance
“…Heparin infusion, starting within 24 h after surgery, has been associated with an increased risk for bleeding before , as in our analysis, whereas the prophylactic use of heparin (5000 IU s.c. twice daily) is reported to be safe . Others reported an increased risk of bleeding after continued VKA therapy as well, but concluded that the indication for VKA therapy was nonmodifiable in certain patients . We can concur this finding since all patients on continued VKA therapy in our analysis had a vital indication for anticoagulation therapy, i.e., due to paroxysmal atrial fibrillation with high CHA2DS2‐VASc scores.…”
Section: Discussionsupporting
confidence: 75%
“…Heparin infusion, starting within 24 h after surgery, has been associated with an increased risk for bleeding before , as in our analysis, whereas the prophylactic use of heparin (5000 IU s.c. twice daily) is reported to be safe . Others reported an increased risk of bleeding after continued VKA therapy as well, but concluded that the indication for VKA therapy was nonmodifiable in certain patients . We can concur this finding since all patients on continued VKA therapy in our analysis had a vital indication for anticoagulation therapy, i.e., due to paroxysmal atrial fibrillation with high CHA2DS2‐VASc scores.…”
Section: Discussionsupporting
confidence: 75%
“…Our current data hint that an initiation of anticoagulation <6 h and an intake of antiplatelet therapy within 24 h after KT are significant predictors of the development of postoperative bleeding in univariable analysis and should possibly be avoided, whenever possible. In accordance with our results, other studies reported an increased risk for bleeding after a continuation of VKA in the perioperative period with urgent indications for continued VKA therapy in certain patients and risk constellations [5,39]. Likewise, in our current study, all patients on continued anticoagulative or antiplatelet therapy had vital indications for anticoagulation therapy, e.g., due to atrial fibrillation with high CHA2DS2-VASc scores, a history of deep venous thrombosis and/or pulmonary embolisms, a history of acute myocardial infarction with stenting of the coronary arteries or a history of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…Initiation of heparin infusion in a therapeutical dose within 24 h after surgery has been associated with an increased risk of bleeding; accordingly, in our current analysis the bleeding risk was increased when heparin was started within the first 6 h postoperatively, whereas the prophylactic use of heparin is reported to be safe [5,6,8]. Interestingly, the use of intraoperative heparin as well as APT per se or in combination with prophylactic doses of heparin were not associated with an increased bleeding risk, which is also underlined by previous studies [5,39]. Hence, according to common clinical practice, heparin seems a good and safe choice for perioperative anticoagulation, whereas the timing and dose of postoperative heparin must be considered with caution.…”
Section: Discussionsupporting
confidence: 79%
“…Only a few prospective studies on interventions to prevent RGT are available, as confirmed by a recent systematic review [ 15 ], and these provide little evidence. Furthermore, the scarce number of retrospective studies also draws conflicting conclusions [ 3 , 9 , 11 , 16 ]. This survey further illustrates the high variation in antithrombotic management strategies in adult KTx, as a result of the paucity of high-quality studies.…”
Section: Discussion/conclusionmentioning
confidence: 99%